Bipolaris hawaiiensis (Bugnicourt ex M.B. Ellis) Uchida & Aragaki - A new record of human pathogenic species of Bipolaris in Bangladesh - Shamsi, Shamim; Yeasmin, Fatema (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(2): 175-178, 2013 (July)